Thyroid cancer in a patient with Lynch syndrome – case report and literature review - Fazekas-Lavu M; Parker A; Spigelman AD; Scott RJ; Epstein RJ; Jensen M; Samaras K (Dove Medical Press, 2017)
Monika Fazekas-Lavu,1 Andrew Parker,2 Allan D Spigelman,3,4 Rodney J Scott,5 Richard J Epstein,6 Michael Jensen,7 Katherine Samaras1,8 1Department of Endocrinology, 2Department of Pathology, St Vincent’s Hospital, Darlinghurst, NSW, Australia; 3Hereditary Cancer Clinic, St Vincent’s Cancer Genetics Service, Darlinghurst, NSW, Australia; 4University of NSW, St Vincent’s Clinical School, Darlinghurst, NSW, Australia; 5Division of Molecular Medicine, Pathology North, John Hunter Hospital and The Hunter Medical Research Institute, Newcastle, NSW, Australia; 6Department of Oncology, 7Department of Oncological Surgery/General Surgery, St Vincent’s Hospital, Darlinghurst, NSW, Australia; 8Diabetes and Metabolism Research Program, Garvan Institute of Medical Research, Darlinghurst, NSW, Australia Abstract: Lynch syndrome describes a familial cancer syndrome comprising germline mutations in one of four DNA mismatch repair genes, MLH1, MSH2, MSH6, and PMS2 and is characterized by colorectal, endometrial, and other epithelial malignancies. Thyroid cancer is not usually considered to be part of the constellation of Lynch syndrome cancers nor have Lynch syndrome tumor gene mutations been reported in thyroid malignancies. This study reports a woman with Lynch syndrome (colonic cancer and a DNA mismatch repair mutation in the MSH2 gene) with a synchronous papillary thyroid cancer. Six years later, she developed metachronous breast cancer. Metastatic bone disease developed after 3 years, and the disease burden was due to both breast and thyroid diseases. Despite multiple interventions for both metastatic breast and thyroid diseases, the patient’s metastatic burden progressed and she died of leptomeningeal metastatic disease. Two prior case reports suggested thyroid cancer may be an extraintestinal malignancy of the Lynch syndrome cancer group. Hence, this study examined the genetic relationship between the patient’s known Lynch syndrome and her thyroid cancer. The thyroid cancer tissue showed normal expression of MSH2, suggesting that the tumor was not due to the oncogenic mutation of Lynch syndrome, and molecular analysis confirmed BRAF V600E mutation. Although in this case the thyroid cancer was sporadic, it raises the importance of considering cancer genetics in familial cancer syndromes when other cancers do not fit the criteria of the syndrome. Careful documentation of other malignancies in patients with thyroid cancer and their families would assist in better understanding of any potential association. Appropriate genetic testing will clarify whether a common pathogenic mechanism links seemingly unrelated cancers. Keywords: cancer genetics, familial cancer syndromes, thyroid and hereditary non-polyposis colorectal cancer